Depot for commercial butane supplier Frank Hennessey - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
The supply and truck depot for commercial butane supplier Frank Hennessey. A large sign painted on the metal storage tank in the center of image reads "Frank Hennessy Bu-Gas Reg. U.S. Pat. Off. Equipment and Installation." Take note of the office and the building for the filling station, both appear to be covered in metal. On the left of the storage tank, a large brick edifice with the sign, "Pacific Coast Pickling Company" stands in the background.